Dielectric and calorimetric signatures of chain orientation in strong and tough ultrafine electrospun polyacrylonitrile. (12th September 2019) - Araujo, Steven; Delpouve, Nicolas; Delbreilh, Laurent; Papkov, Dimitry; Dzenis, Yuris; Dargent, Eric
Abstract: Ultrafine diameter fibers of polyacrylonitrile (PAN), obtained from electrospinning, have huge potential for structural applications since they exhibit an unusual combination of strength and toughness. However, the difficulty to characterize their supramolecular architecture limits their production at the industrial scale. In this work, the glass transition of electrospun nanofiber mats of PAN was investigated by means of thermal analysis techniques. Modulated temperature differential scanning calorimetry (MT–DSC) and dielectric relaxation spectroscopy (DRS) were used, and relaxation parameters characteristic of the glass transition were obtained. Reduction in average fiber diameter resulted in broadening of the glass transition and a shift of its midpoint to higher temperatures as observed by MT–DSC, revealing additional level of constraints in the amorphous phase. The DRS curves, obtained above the calorimetric signature of the glass transition, superimpose independently on the fiber diameter. This result, which contrasts with MT–DSC observations, shows that the constraint of mobility evidenced at the glass transition, is suppressed when driving the fiber mat to higher temperatures. The dielectric strength increases with temperature, revealing an increase in the density of dipoles participating to the relaxation dynamics. This result, commonly attributed to the progressive mobilization of initially constrained amorphous phase, supports the hypothesis that electrospinning process induces higher level of polymer chain orientation at small fiber diameters, which fades away when crossing the glass transition. The orientation impacts the temperature dependence of the relaxation time close to the glass transition, as it shows higher deviation from Arrhenius behavior with the decrease of the fiber diameter. This leads to an increase of the fragility index which comes in opposition to the decrease in the cooperativity length, estimated from the temperature fluctuation approach of the cooperative rearranging region (CRR) concept. To explain this result, both volume and thermal contributions of the fragility index have been calculated, and a strong increase in the thermal contribution has been observed for the most oriented material. This result is interpreted as a signature of an increase in the polymer chain rigidity. Graphical abstract: Image 1 Highlights: Fiber mats of polyacrylonitrile were obtained from electrospinning. Relaxation dynamics were investigated from thermal analysis. Cooperativity decreases when reducing the average fiber diameter. In contrast the thermal contribution to fragility increases. Both changes were attributed to the orientation of polymer chains.